Masalah infeksi Palpebra pada Lanjut Usia - Amalia, Husnun; Pratiwi, Megawati Yulia Wina; Mustopa, Ita Tazkiatul Izzati (Jurnal Biomedika dan Kesehatan, 2024)
Blepharitis is an eyelid infection that increases in incidence with age. This infection can cause anterior and posterior blepharitis and is caused by bacteria, viruses, fungi, and parasites. The most common bacteria that cause blepharitis is Staphylococcus. Blepharitis that is not caused by infection is allergic blepharitis. The pathophysiology of anterior blepharitis is the occurrence of bacterial colonization that triggers an excessive inflammatory response, while in posterior blepharitis it is mainly due to a decrease in the quality of the meibomian glands which causes dry eye and causes friction on the conjunctiva and cornea, causing inflammation. Symptoms of blepharitis are discomfort on the eyelid's surface such as itching, burning, stinging, watery eyes, and others. Risk factors for this infection include seborrheic dermatitis, acne rosacea, contact allergies, diabetes mellitus, chemical irritation, poor hygiene, low socioeconomic status, cosmetics, and the elderly. Diagnosis can be made based on anamnesis and ophthalmological examination which a general practitioner or eye specialist can perform. Based on the diagnosis, further management is given to avoid complications. The management that can be given is maintaining eyelid hygiene, warm compresses, not rubbing the eyes, and giving topical antibiotics (in anterior blepharitis) which can be added with systemic antibiotics (posterior blepharitis). Complications that can occur are eyelash abnormalities, lacrimal punctum malposition, eyelid malposition, recurrent hordeolum, keratitis, dry eye, keratopathy, corneal ulcers, and corneal opacities that can cause impaired visual function.